IMPROVING THE BASIC MOVEMENT OF BACK BOLSTERS USING THE TPACK-BASED PBL MODEL FOR GRADE V STUDENTS OF SD NEGERI SIEM, ACEH BESAR DISTRICT - Alazzraq, Ali Salim Ali; Pranata, Didi Yudha; Khairulrijal, Khairulrijal (Teunuleh Publisher, 2022)
Physical education, health and sports is a very complete subject because it is able to develop all aspects that exist in students. Elementary school students are students who must be well shaped by all aspects that exist in themselves, namely aspects of skills, social, emotional and personality. However, at SD Negeri Siem, in class V, there is a problem, namely the back roll material. The problem that arises is in the aspect of student skills, students have not been able to do a back roll well. Based on the existing problems, an idea was born as a solution to the problem, namely Improving the Back Rolling Basic Motion Using the TPACK-based PBL model for Class V students of SD Negeri Siem, Aceh Besar District. The formulation of the problem is as follows; Can the TPACK-based PBL model improve the basic back bladder movement for Class V students at SD Negeri Siem, Aceh Besar District? The purpose of this study was to find out that the TPACK-based PBL model could improve the basic movements of the back bladder for fifth graders at SD Negeri Siem, Aceh Besar District. This research uses classroom action research method. The results of this study, namely in Cycle I, it was known that the number of students was 26 people with a total score of 1775, the average value of students was 68.27 with the highest score of 80 and the lowest score of 50. 50%) and 13 people (50%) who did not complete it. And the second cycle is known that the number of students as many as 26 people with a total score of 1985, the average value of students is 76.35 with the highest score of 90 and the lowest score of 50. So it can be seen also that the students who completed are 24 people (92.31% ) and 2 people who did not complete it (7.69%). The conclusion is that the TPACK-Based PBL Model can improve the basic movements of the back bladder for Class V students of SD Negeri Siem, Aceh Besar District.